2018
DOI: 10.1002/lno.11056
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton responses to the 2014–2016 warming anomaly in the northeast subarctic Pacific Ocean

Abstract: Significant changes in the abundance and composition of phytoplankton were observed along Line P in the northeast subarctic Pacific as a result of a rapid warming of surface waters in 2014–2015. This feature, labeled “the blob,” reached ~ 4°C above normal and restricted winter ocean–surface nutrient renewal due to increased stratification. As a result, surface nutrients were the lowest observed and nitrate depletion in summer extended farther offshore than in the last three decades. Within this nitrate‐deplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 45 publications
11
59
0
Order By: Relevance
“…The apparent result was the lowest chlorophyll estimate for April through August 2016 from MODIS satellites in the 14 yr record (2003− 2016) (Hopcroft et al 2018). A similar response to the Pacific MHW with low nutrients and chlorophyll was recently documented in British Columbia (Peña et al 2018).…”
Section: Discussionsupporting
confidence: 79%
“…The apparent result was the lowest chlorophyll estimate for April through August 2016 from MODIS satellites in the 14 yr record (2003− 2016) (Hopcroft et al 2018). A similar response to the Pacific MHW with low nutrients and chlorophyll was recently documented in British Columbia (Peña et al 2018).…”
Section: Discussionsupporting
confidence: 79%
“…In 2014 and 2015, the northern Gulf of Alaska exhibited low zooplankton abundance (McKinstry & Campbell, 2018). The warm anomalies impacted the Bering Sea from 2014 until 2016 by shifting phytoplankton blooms to early spring (Stabeno et al, 2017), similar to the early increase in phytoplankton abundance observed in the Gulf of Alaska in 2014 (Peña et al, 2019) and early NCP from this work (Figure 4c). The development of the Arc pattern along the west coast of United States between 2014 and 2015 altered the local phytoplankton community structure (Du & Peterson, 2018), with elevated SSTs stimulating harmful algae blooms in the northern California Current (McKibben et al, 2017;Zhu et al, 2017).…”
Section: Environmental Consequences Of the 2013-2016 Warm Events And supporting
confidence: 75%
“…Our results show that early initiation of NCP in spring 2014 was promoted by a shallow and stable MLD condition induced by the first warm event (Figure 1a). The enhanced production could have been related to the high phytoplankton biomass, such as proposed by Alexander et al (2008) and observed by Peña et al (2019). Indeed, similar initial upper ocean conditions resulted in high NCP observed in summer 2009 (Figures 4 and 5).…”
Section: Considering the Difference In Net Organic Carbon Production supporting
confidence: 55%
See 2 more Smart Citations